Evaluation of epicardial fat tissue thickness and aortic stiffness in patients with gestational diabetes mellitus - Akın, Melike Nur; Kasap, Burcu; Akın, Fatih; Sezgin, Burak; Altun, İbrahim; Camuzcuoğlu, Aysun; Deveer, Rüya; Turhan, Nilgun (Perinatal Medicine Foundation, 2021)
Objective We aimed to assess the relationship between gestational diabetes mellitus and coronary artery disease by measuring epicardial fat tissue thickness and aortic stiffness in pregnant women diagnosed with gestational diabetes mellitus. Methods 28 pregnant women diagnosed with gestational diabetes mellitus and 25 pregnant women without gestational diabetes mellitus were included in the research. Body mass index, laboratory values, blood pressure measurements and obstetric history findings of the study population were recorded. All participants of the study population were evaluated with transthoracic echocardiography between 24 and 28 weeks of gestational period. The measurement of epicardial fat tissue thickness was taken and aortic stiffness index was also calculated. Results The age, gravidity, parity and obstetric history of the two groups were similar. Epicardial fat tissue thickness was found significantly higher in gestational diabetes mellitus group than control group (0.416 cm and 0.336 cm, respectively; p<0.001). However, no significant difference was found in aortic stiffness measurements of the two groups (p=0.079). Conclusion According to the results of our study, epicardial fat tissue thickness was found to be statistically significantly higher in pregnant women with gestational diabetes mellitus compared to the control group. The fact that no difference was detected in other cardiovascular parameters suggests that measurement of epicardial fat tissue thickness in gestational period may be a beneficial adjunctive tool in early detection of gestational diabetes mellitus.